Pelestarian Desa Budaya Batu Urip Sebagai Sejarah Budaya Lokal Kota Lubuk Linggau - Susilo, Agus; Asmara, Yeni (Fakultas Adab dan Humaniora UIN Raden Fatah, 2023)
The development of an increasingly advanced era in this digital era has given a lot of color to culture in Indonesia, especially in Lubuklinggau City. The purpose of this research is to determine the preservation of Batu Urip cultural village as a local culture in Lubuklinggau City. The research method used is historical research method using historical method. In this research, researchers use descriptive qualitative research studies to analyze the data that has been obtained. Data sources were obtained through field observations developed with book and journal sources as reference materials. The results of this study, namely: The preservation of Batu Urip Cultural Village as a local Cultural Heritage of Lubuklinggau City History is Batu Urip Village is a village in Lubuklinggau City that is still terawatt in developing the culture of its people The study of cultural history in Batu Urip Village continues to grow rapidly. This is because in Batu Urip Village there are historical sites and preservation of local culture such as Mandi Kasai which is still well preserved. Studies related to the history of this local culture can develop with the enthusiasm of the people who still maintain pure customs. In addition, the preservation of history and culture in Batu Urip has also been developed by students, researchers and the SARISEJAYA Community as a history and arts community in Lubuklinggau City. All of them strive to support Batu Urip as a cultural heritage village that has historical, artistic and cultural values. The conclusion is that the preservation of Batu Urip's local cultural history should always be vigorously supported. Cooperation with the community and history students will have a positive impact on the development of local cultural heritage in Batu Urip, Lubuklinggau City.